Application of One-Dimensional Semiclassical Transition State Theory to the CH3OH+H -> CH2OH/CH3O+H2 Reactions - Shan, X; Clary, D (Royal Society, 2018)
The rate constants of the two branches of H-abstractions from CH3OH by H atom and the corresponding reactions in reverse direction are calculated using the one-dimensional semiclassical transition state theory (1D SCTST). In this method, only the reaction mode vibration of the transition state (TS) is treated anharmonically, while the remaining internal degrees of freedom are treated as they would have been in a standard transition state theory calculation. A total of 8 ab initio single point energy calculations are performed in addition to the computational cost of a standard transition state theory calculation. This allows a second-order Richardson extrapolation method to be employed to improve the numerical estimation of the third and fourth order derivatives, which in turn are used in the calculation of the anharmonic constant. Hindered-rotor vibrations are identified in the equilibrium states of CH3OH and CH2OH, and the transition states of the reactions. The partition function of the hindered-rotors are calculated using both a simple harmonic oscillator model and a more sophisticated one-dimensional torsional eigenvalue summation (1D TES) method. The 1D TES method can be easily adapted in 1D SCTST computation. The resulting 1D SCTST with 1D TES rate constants show good agreement to previous theoretical and experimental works. The effects of the hindered-rotor on rate constants for different reactions are also investigated.